Efficiency analysis of organized industrial zones in Eastern Black Sea Region of Turkey. (December 2019) - Dursun, Mehtap; Goker, Nazli; Tulek, Burcu Deniz
Abstract: Organized Industrial Zones (OIZs) are the production areas of goods and services that are established to provide planned industrialization and planned urbanization by structuring the industry in suitable areas, to prevent environmental problems, and to provide efficient use of resources. The aim of this study is to propose a decision-making model based on data envelopment analysis (DEA) to evaluate the relative efficiencies of OIZs located in the Eastern Black Sea Region of Turkey. First, the efficiency score of each alternative is determined by employing a DEA formulation with interval data. Second, a common weight DEA-based formulation is applied in order to obtain common set of weights and provide ranking results with an improved discriminating power in imprecise nature. In this study, the best performing OIZ alternative, which performs in Eastern Black Sea region of Turkey, is identified based on the approach proposed by Salahi et al. [1]. The DEA-based model developed by Salahi et al. [1] is improved by modifying a constraint. In order to demonstrate the robustness of the application, two numerical illustrations are given. The first example compares the results obtained by the formulation addressed in Salahi et al. [1] and the improved model; while second numerical illustration provides a case study conducted in Eastern Black Sea region of Turkey. Highlights: A DEA-based MCDM model is presented to provide performance assessment of OIZs located in Eastern Black Sea Region of Turkey. Imprecise DEA-based mathematical programming model developed by Salahi et al. (2016) is improved by modifying a constraint. The proposed approach, which generates common set of weights, can be employed in the presence of crisp and interval data. Two numerical illustrations are provided in order to demonstrate the robustness of the application. The first example provides a comparative analysis, whereas the second includes a real world application in Turkey.